Chronic Subdural Hemorrhage Associated With an Arachnoid Cyst After Sports Injury in Childhood: A Case Report and the Literature Review. Issue 4 (November 2016) - Yaldiz, Can; Kacira, Tibet; Ceylan, Davut; Asil, Kiyasettin
Abstract : Arachnoid cysts and chronic subdural hemorrhages are very common in brain surgeries. Our case, a 15-year-old male amateur footballer, was admitted to our emergency unit following a minor blow. Clinical examinations found chronic subdural hemorrhage associated with an arachnoid cyst. Chronic subdural hemorrhage was drained using 2 burr holes and full recovery was achieved clinically. We present this case because there are rare reports of similar cases in the literature.